COOPERATION PRACTICES OF MENGARUNAKAN: EMPIRICAL EVIDENCE OF MUSAQAH AGREEMENTS IN THE ECONOMY OF KALIMANTAN SOCIETY - Rivani, Muhammad; Rani, Muhammad; Akbar, Wahyu; Ardiansyah, Mawar (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
The purpose of this study is to describe and analyze cooperation with the mengarunakan system on rubber plantations carried out by the people of Putai Village, Dusun Tengah District, East Barito Regency in accordance with the Islamic Economic Perspective. This study is a field study with qualitative descriptive, contextual, and ethnographic research methods. The subjects in this study were 5 rubber plantation land owners, 5 sharecroppers, and 1 community leader in Putai Village. The data collection technique in this study used participant observation, interview and documentation techniques which were then analyzed using data collection, data reduction, data presentation and conclusion drawing techniques. The results of this study are (1) The implementation of cooperation with the mengarunakan system in Putai Village is that the agreement is carried out verbally. For rubber plantation land and rubber trees come from the landowner, while all rubber plantation maintenance costs such as fertilizer, medicine, land clearing, gardening equipment and so on related to land cultivation are the responsibility of the rubber plantation sharecroppers. The distribution of results carried out by the Community in Putai Village is in the form of money obtained from the sale of the harvest from the rubber plantation, the results of the sale will be divided by one third and the distribution of the results is 1/3 for the plantation owner and 2/3 for the farmer. (2) According to the Islamic Economic Perspective, cooperation with the granting system carried out by the Putai Village Community is included in one form of plantation profit sharing agreement in Islamic economics which is called musaqah and it can be said that the practice of profit sharing carried out is valid according to Islamic economic rules.